Persistent Luminescence: Temperature Dependency of Trap‐Controlled Persistent Luminescence (Laser Photonics Rev. 14(8)/2020). Issue 8 (13th August 2020) - Du, Jiaren; Feng, Ang; Poelman, Dirk
Abstract : The relation between the optimum working temperature of persistent 'glow‐in‐the‐dark' phosphors and their thermoluminescence glow curve is investigated. In article number 2000060, Jiaren Du, Ang Feng, and Dirk Poelman present new perspectives for designing and screening persistent phosphors for various ambient conditions, and beyond.